Differential effects of physical activity on behavioral and prefrontal responses during repetitive inhibitory control in older adults - Lee, Jae-Hoon; Lee, Minchul; Ha, Min-Seong (Frontiers in Aging Neuroscience, 2025)
ObjectivesThis study aimed to investigate the effects of physical activity levels on response time and prefrontal activation during repetitive performance of the Stroop task in older adults.MethodsWe examined how physical activity influences selective inhibition and neurophysiological responses in the prefrontal cortex. Community-dwelling adults aged 65–85 years were classified into physically active (PA, n = 18) and physically inactive (PI, n = 19) groups using the International Physical Activity Questionnaire (IPAQ). On a single experimental day, participants completed the Stroop task in three consecutive blocks within one session. Participants completed the Stroop task three times. Reaction time and oxygenated hemoglobin (HbO) levels in the prefrontal cortex were measured using functional near-infrared spectroscopy (fNIRS) and analyzed by the Brodmann area.ResultsA two-way repeated-measures analysis of variance revealed significant time, group, and interaction effects on reaction time (p < 0.05). The PA group showed a significant decrease in reaction time across repetitions (p < 0.001), whereas no such change was observed in the PI group. In terms of brain activation, HbO levels increased significantly over time in the left dorsolateral prefrontal cortex and the right ventrolateral prefrontal cortex (p < 0.05), although no significant group differences were observed.ConclusionRegular physical activity may enhance cognitive adaptability and selective inhibition in older adults. Behavioral improvements were more evident than neural differences between the groups, highlighting the potential of everyday physical activity to support cognitive resilience in aging. This study provides neurophysiological evidence supporting the integration of physical activity into cognitive intervention strategies for older populations.